How Does Diabetes Impair Penile Tissues during Erectile Dysfunction? - Wu, Yi-Xing; Yang, Chun-Tao; Li, Na; Zheng, Xue; Li, Xiang; Zhang, Hui; Shen, Jie (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Erectile dysfunction (ED) is a significant but underestimated complication during diabetes mellitus (DM). Currently, few special treatments are available clinically due to the lack of specific therapeutic targets. Genomic analysis can be helpful to find potential targets. In this study, the gene expression under diabetic ED condition was analyzed using a gene array, and the significance of the outcomes was evaluated through clinical data. Methods: The expressions of 15923 genes were analyzed using R software. Differential expression genes (DEGs) were identified through the constructed volcano plot. The function enrichment of Gene Ontology (GO) and KEGG was screened with the DAVID online tool. The interaction between these DEGs was revealed through constructing a protein-protein interaction network and the hub genes were uncovered using the STRING and Cytoscape tool. Lastly, the data of diabetic ED patients were applied to verify the bioinformatics findings. Results: The study showed that 75 genes in the rat penile tissues were upregulated, while 97 genes were downregulated on the diabetic ED condition. These genes were mainly involved in extracellular matrix composition, collagen fibril organization, as well as protein digestion & absorption. Additionally, insulin-related signaling pathways were affected. The clinical analysis indicated that insulin resistance was associated with the diabetic ED severity. Notably, the bioinformatics analysis also suggested that ferroptosis pathway was probably activated under the diabetic ED condition. Conclusion: The impaired protein synthesis induced by deficient insulin signaling is an important cause of the diabetic ED. The improvement of protein synthesis through restoring insulin function may be potentially useful for diabetic ED therapy.
Keywords: insulin resistance